Growing in Mixed Stands Increased Leaf Photosynthesis and Physiological Stress Resistance in Moso Bamboo and Mature Chinese Fir Plantations - Peng, Chunju; Song, Yandong; Li, Chong; Mei, Tingting; Wu, Zhili; Shi, Yongjun; Zhou, Yufeng; Zhou, Guomo (Frontiers in Plant Science, 2021)
Mixed-stand plantations are not always as beneficial for timber production and carbon sequestration as monoculture plantations. Systematic analyses of mixed-stand forests as potential ideal plantations must consider the physiological-ecological performance of these plantations. This study aimed to determine whether mixed moso bamboo (Phyllostachys pubescens (Pradelle) Mazel ex J. Houz.) and Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.) stands exhibited better physiological-ecological performance than monoculture plantations of these species. We analysed leaf photosynthesis, chlorophyll fluorescence, antioxidant enzyme activities, chlorophyll content and leaf chemistry in a moso bamboo stand, a Chinese fir stand and a mixed stand with both species. The results showed that both species in the mixed stand exhibited significantly higher leaf net photosynthesis rate (Amax), instantaneous carboxylation efficiency (CUE), chlorophyll content, maximum quantum yield of photosynthesis (Fv/Fm), photochemical quenching coefficient (qP), PSII quantum yield (Y(II)), leaf nitrogen content, and antioxidant enzyme activities than those in the monoculture plantations. However, the nonphotochemical quenching (NPQ) in Chinese fir and two-year-old moso bamboo was significantly lower in the mixed stand than in the monocultures. In addition, the water use efficiency (WUE) of Chinese fir was significantly higher in the mixed stand. The results suggest that the increase in leaf net photosynthetic capacity and the improved growth in the mixed stand could be attributed primarily to the (i) more competitive strategies for soil water use, (ii) stronger antioxidant systems, and (iii) higher leaf total nitrogen and chlorophyll contents in the plants. These findings suggest that mixed growth has beneficial effects on the leaf photosynthesis capacity and physiological resistance of moso bamboo and Chinese fir.